Chronic Timed Sleep Restriction Attenuates LepRb-Mediated Signaling Pathways and Circadian Clock Gene Expression in the Rat Hypothalamus - Sun, Qi; Liu, Yang; Wei, Wei; Wu, Dan; Lin, Ren; Wen, Deliang; Jia, Lihong (Frontiers in Neuroscience, 2020)
The sleep duration of adolescents has continued to decline over the past twenty years. Sleep insufficiency is one of the most important risk factors for obesity, but the mechanisms underlying the association are unclear. Therefore, the hypothalamic-regulated mechanisms of appetite and the circadian clock gene expression were examined in sleep-restricted rats. Rats aged 7 weeks were randomly divided into two groups: the control group and sleep restriction group (7 rats/group), rats were sleep-restricted for 4 weeks. Body weight gain and amount of food/water consumption was quantified. The expression of genes or proteins which regulated appetite and energy metabolism via leptin receptor signaling and the circadian clock in the hypothalamus were assessed. Chronic sleep restriction induced increased food intake and weight gain in adolescent and young adult rats from the second week of initiation of sleep restriction. Phosphorylation of Janus kinase 2 (JAK2)/Signal transducer and activator of transcription 3 (STAT3) were decreased, although levels of circulating leptin or leptin receptor expression were unaltered. Furthermore, insulin receptor substrate (IRS)/phosphoinositide 3-kinase (PI3K)/AKT/mTOR and forkhead box O1 (FoxO1) signaling pathways were also compromised. Moreover, core circadian clock genes were also decreased in the sleep restriction group compared with the control. Chronic timed sleep restriction induced hyperphagic behaviors, attenuated leptin receptor mediated signaling pathways, and depleted the expression of circadian clock gene in the hypothalamus of adolescent and young adult rats.